Supporting Constructive Engagement between the Government of Yemen and CSOs : Partnership for Development Knowledge Conference - World Bank (Washington, DC, 2014)
This is a post conference summary of the Partnership for Development Knowledge Conference held in Yemen from March 4-6, 2014. The report summarizes the discussions that took place during various conference sessions and also some of the outcomes and agreements reached. Following a rich and open dialogue, important outcomes of the conference included a set of recommendations jointly formulated by the government technical teams and Civil Society Organization(s), or CSO representatives. They also agreed on a series of future actions, including the following: build on working group outcomes and discussions with the Ministry of Planning and International Cooperation to determine the 3-4 priority sectors in which more sector-specific dialogue needs to take place. Preparations and groundwork for sector-specific dialogue, building on the conference outcomes, will continue via technical discussions with relevant Sector Ministries. A possible knowledge visit to India by a small government technical team will be explored, with a focus on issues of social accountability. Sector dialogue sessions will be implemented after Ramadan 2014 and will focus on sectors that were recommended by the working groups. Dialogue sessions will support the development of sector-specific action plans that identify concrete opportunities for partnership between specific ministries and CSOs operating within the sector. In conclusion, the conference provided an ideal background to prepare for the sector-level dialogue sessions. These sessions will be facilitated under the next phase of the World Bank funded Government-CSOs Partnership Project.